The Limits of Modal Knowledge - Rehan P. Visser (Principia: An International Journal of Epistemology)
Modal agnosticism is the view that we must be agnostic about whether things could have turned out differently. I argue that claims about unrealised possibilities (what I term ‘merely metaphysical modal claims’) are not justified by our modal intuitions, nor are they justified by any of the means proposed by philosophers. It follows that we do not have merely metaphysical modal knowledge, and that we must adopt modal agnosticism.